90.0k views
1 vote
Which expression is equivalent to (3x^2-7)?

A. (2x^2-11)-(x^2+4)
B. (5x^2-6)-(2x^2-1)
C. (10x^2-4)-(7x^2+3)
D. (15x^2-8)-(18x^2+1)

1 Answer

7 votes

Answer:

C.
(10x^2-4)-(7x^2+3)

Explanation:

In option A,


(2x^2-11)-(x^2+4)= 2x^2 - 11 - x^2 - 4 = x^2 -15

Since,


(x^2-15)\\eq (3x^2-7)

Option A is incorrect.

In option B,


(5x^2-6)-(2x^2-1)= 5x^2-6-2x^2+1 = 3x^2 -5

Since,


(3x^2-5)\\eq (3x^2-7)

Option B is incorrect.

In option C,


(10x^2-4)-(7x^2+3)= 10x^2-4-7x^2-3 = 3x^2 -7

Option C is correct.

In option D,


(15x^2-8)-(18x^2+1)= 15x^2-8-18x^2-1= -3x^2 -9

Since,


(-3x^2 -9)\\eq (3x^2-7)

Option D is incorrect.

User Gimlichael
by
6.8k points